Antagonistic activity of endo‐β‐1, 3‐glucanase from a novel isolate, Streptomyces sp. 9X166, against black rot in orchids. (17th February 2016) - Sakdapetsiri, Chatsuda; Fukuta, Yasuhisa; Aramsirirujiwet, Yaovapa; Shirasaka, Norifumi; Kitpreechavanich, Vichien
Abstract : A total of 123 actinomycetes was isolated from 12 varieties of wild orchids and screened for potential antagonistic activity against Phytophthora, which causes black rot disease in orchids. In vitro and in vivo experimental results revealed that Streptomyces sp. strain 9X166 showed the highest antagonistic activity; its β‐1, 3‐glucanase production ability was a key mechanism for growth inhibition of the pathogen. PCR amplification and DNA sequencing of the 16S ribosomal RNA gene allowed the identification of this strain, with high similarity (99.93%) to the novel species Streptomyces similaensis . The glucanase enzyme, purified to homogeneity by anion exchange and gel filtration chromatography, showed a specific activity of 58 U mg −1 (a 3.9‐fold increase) and yield of 6.4%. The molecular weight, as determined by SDS‐PAGE and gel filtration, was approximately 99 and 80 kDa, respectively, suggesting that the enzyme was a monomer. The purified enzyme showed the highest substrate specificity to laminarin, indicating that it was β‐1, 3‐glucanase. The hydrolyzed products of cello‐oligosaccharides suggested that this enzyme was endo‐type β‐1, 3‐glucanase. Streptomyces sp. 9X166 culture filtrate, possessing β‐1, 3‐glucanase activity, could degrade both freeze‐dried and living mycelium. This is the first report on a β‐1, 3‐glucanase‐producing Streptomyces sp. that could be an effective biocontrol agent for black rot disease in orchids.